Study of the potential for Streptomyces coelicolor to produce bioactive compounds from flower waste as a sustainable feedstock - Sarah Jennings; Sean Craig; Samantha Bryan; Parimala Shivaprasad (Sustainable Chemistry for Climate Action)
Agricultural and horticultural industries across the globe lead to vast quantities of waste, often disposed of indiscriminately both at the point of production and by consumers. These wastes can lead to pollution of local environments and eco-systems, such as those in India affected by the 800 thousand tonnes of floral waste annually. Floral waste is rich in compounds useful in the personal care and pharmaceutical industries, such as terpenoids and other phenolics. These compounds are synthesised and modified by many microorganisms, including Streptomyces, the microorganisms responsible for many anti-cancer and antibiotic drugs used today. Streptomyces species are also known to produce lignocellulolytic enzymes, leading to the degradation of plant matter. This study aims to explore whether Streptomyces can utilise a semi-solid flower media whilst producing industrially useful bioactive compounds from natural floral compounds. Blended flowers in ISP4 media were inoculated with Streptomyces coelicolor M145 and sampled regularly over a 6-week aerobic incubation period. A range of bioactive compounds were identified through GC–MS analysis of the aqueous media, providing evidence that under the correct conditions floral waste has potential as a sustainable feedstock.